METHOTOLOGICAL PRINCIPLES OF ANALYZING THE COMPETITIVENESS OF WHOLESALE TRADE ENTERPRISES (Development Service Industry Management, 2025)
The article, using the example of wholesale grain trade, reveals methodological approaches to the study of the competitiveness of domestic enterprises in the context of European integration. It is substantiated that the level of competitiveness is shaped by a combination of internal factors – such as financial stability, efficiency of resource utilization, and the level of innovation and investment activity – as well as external conditions, including market conjuncture, development of logistics infrastructure, and compliance with regulatory policies and EU standards. Existing approaches to assessing the competitive positions of enterprises are generalized: quantitative methods ensure objectivity of results and comparability, qualitative methods allow for consideration of strategic factors and the specific features of enterprise functioning, while strategic methods are oriented towards forecasting trends and modeling development scenarios. The systematization of these approaches has made it possible to identify their advantages and limitations and to justify the expediency of combining different tools. Particular attention is paid to the index method, which combines comprehensiveness and flexibility, enables comparison and ranking of enterprises, and identifies “bottlenecks” in their activities. The calculation of integral competitiveness indices of wholesale grain trade enterprises was carried out using additive and multiplicative approaches, which ensured the verification of result stability and increased the reliability of conclusions. The practical significance of the obtained results lies in their applicability for strategic planning, optimization of management decisions, and formation of competitive advantages of Ukrainian grain traders.
Keywords: agrarian sector; competitiveness; wholesale trade; grain; enterprise; logistics; analysis; method; index method; modeling; European integration